Interaction of different tRNAs with translation elongation factors 1A from lower and higher eukaryotes - Futernyk, P.V.; Negrutskii, B.S.; El'skaya, A.V. (Вiopolymers and Cell, 2009)
The work is aimed at confirmation of earlier assumed mechanism of tRNA channeling. Methods. The methods of band shift assay and Forsters resonance energy transfer were used. Results. The affinities of mammalian tRNAs for two tissue specific isoforms of elongator factor eEF1A1 and eEF1A2 were compared. For the first time we have shown the ability of yeast eEF1A*GDP to form non-canonical ternary complex with deacylated tRNAs. The complexation of eukaryotic eEF1A with initiator tRNA, of both bacterial and mammalian origin, was also demonstrated. Conclusions. The formation of the non-canonical complexes of eEF1A*GDP with deacylated tRNAs is common for higher and lower eukaryotes, which is in favor of universality of eukaryotic tRNA-channeling. Мета. Підтвердити запропонований раніше механізм каналювання тРНК. Методи. Зсув смуги в поліакриламідному гелі та Форстерівське резонансне перенесення енергії (FRET). Результати. Оцінено спорідненість тРНК ссавців з двома тканино-специфічними ізоформами фактораe еEF1A1 та eEF1A2. Вперше показано формування неканонічних потрійних комплексів дріжджового eEF1A*GDP з деацильованими тРНК. Продемонстровано також комплексоутворення еукаріотного eEF1A з ініціаторною тРНК ссавців і бактерій. Висновки. Формування неканонічних комплексів eEF1A*GDP з деацильованими тРНК є загальним для вищих і нижчих еукаріотів, що підтверджує універсальність еукаріотного каналювання тРНК Цель. Подтвердить предложенный ранее механизм каналирования тРНК. Методы. Сдвиг полосы в полиакриламидном геле и Форстеровский резонансный перенос энергии (FRET). Результаты. Оценено сродство тРНК млекопитающих с двумя тканеспецифическими изоформами фактора eEF1A1 и eEF1A2. Впервые показано формирование неканонических тройных комплексов дрожжевого eEF1A*GDP с деацилированными тРНК. Также продемонстрировано комплексообразование эукариотного eEF1A с инициаторной тРНК млекопитающих и бактерий. Выводы. Формирование неканонических комплексов eEF1A*GDP с деацилированными тРНК является общим для высших и низших эукариотов, что подтверждает универсальность эукариотного каналирования тРНК.